Systems of linear equations and reduced matrix in a linear algebra course for economics studies - Dniestrzański, Piotr (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
The article presents two elements of the concept of a linear algebra lecture for economics studies. It attempts to demonstrate the significant role of ordering of the lectured content – with a focus on starting the lecture with systems of linear equations, and shows the considerable benefits of introducing the concept of the reduced row echelon form of matrix as one of the most useful concepts of linear algebra.
Didactics of Mathematics, 2012, Nr 9 (13), s. 43-54
Keywords: linear algebra; reduced matrix; linear equations; economic studies; standards of teachings